Plasma levels of thyroxine, prolactin, and cortisol in migrating and resident wild arctic char, Salvelinus alpinus - Høgåsen, Helga Rachel; Prunet, Patrick (Canadian Journal of Fisheries and Aquatic Sciences, 1997)
The study was performed on 14-49 cm wild arctic char, Salvelinus alpinus. Plasma thyroxine concentration was twice as high in upstream and downstream migrants (3.8 and 4.0 ng/mL, respectively) as in non-migrants (1.7 ng/mL), supporting the prevailing view that thyroid hormones are stimulatory to both upstream and downstream migration in wild anadromous salmonids. The stimulation of downstream migration by thyroid hormones is suggested to depend on the low feeding state of wild smolts. Plasma prolactin concentration was lower in downstream migrants (10.3 ng/mL) than in non-migrants sampled during the period of downstream migration (16.2 ng/mL), suggesting a possible role for this hormone in repressing seaward migration. Plasma cortisol level was twice as high in upstream migrants (464 ng/mL) as in downstream migrants (244 ng/mL) trapped in a standardized manner. Higher interrenal capacity or responsiveness in upstream migrants may increase their ability to mobilize energy stores. In upstream-migrating females, plasma prolactin concentration was positively correlated with the gonadosomatic index, suggesting a role for prolactin in early sexual maturation. Body length, which was correlated with numbers of migrations, was found to be related only to plasma thyroxine concentration in downstream migrants.